Association between glycated hemoglobin/high-density lipoprotein ratio and nonalcoholic fatty liver disease in a U.S. nondiabetic population: a cross-sectional study based on NHANES 2017–2020 data - Xiaowei Zheng; Huimin Wang (BMC Gastroenterology)
Abstract Aims The purpose of this research was to explore the relationship between the glycated hemoglobin/high-density lipoprotein (HbA1c/HDL-C) ratio and nonalcoholic fatty liver disease (NAFLD) in non-diabetic adults in the United States. Methods Using pertinent variables gathered from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) database, we performed a cross-sectional study including 5,485 adult U.S. citizens. Data were analyzed using multifactor logistic regression, smoothed curve fitting, subgroup, and interaction analyses. Results Among the 5485 individuals included, there was a significant positive correlation between NAFLD and HbA1c/HDL-C ratio. After adjusting for all covariates, the probability of having NAFLD increased significantly for each unit increase in the log-transformed ratio of this [2.39 (1.94, 2.93)]. Furthermore, we discovered a nonlinear relationship with an inflection point of 1.43 between the ratio and NAFLD. In the end, subgroup analyses revealed a significant interaction between the correlation of this ratio and NAFLD, stratified by the presence or absence of comorbid coronary artery disease (interaction P < 0.05). Conclusion Our study demonstrated a significant positive correlation between the HbA1c/HDL-C ratio and NAFLD risk in non-diabetic individuals. Thus, the ratio may be a useful correlate of NAFLD risk. Monitoring this ratio through routine physical examination may help to identify high-risk individuals early and then take lifestyle interventions (e.g., dietary modification, increased exercise, etc.) or pharmacological treatments to prevent the development of NAFLD.